Effects of placentophagy on maternal salivary hormones: A pilot trial, part 1. Issue 4 (August 2018) - Young, Sharon M.; Gryder, Laura K.; Cross, Chad; Zava, David; Kimball, David W.; Benyshek, Daniel C.
Abstract: Background: Recent studies show that human placenta, processed and encapsulated for postpartum consumption, contains a host of trace minerals and hormones that could conceivably affect maternal physiology. Our objective was to investigate whether salivary hormone concentrations of women ingesting their own encapsulated placenta during the early postpartum differed from those of women consuming a placebo. Methods: Randomly assigned participants (N = 27) were given a supplement containing either their dehydrated and homogenized placenta (n = 12), or placebo (n = 15). Saliva samples were collected during late pregnancy and early postpartum. Samples of participants' processed placenta, and the encapsulated placebo, were also collected. Hormone analyses were conducted on all samples utilizing liquid chromatography–tandem mass spectrometry. Results: There were no significant differences in salivary hormone concentrations between the placenta and placebo groups post-supplementation that did not exist pre-supplementation. There were, however, significant dose–response relationships between the concentration of all 15 detected hormones in the placenta capsules and corresponding salivary hormone measures in placenta group participants not seen in the placebo group. The higher salivary concentrations of these hormones in the placenta group reflects the higher concentrations of these hormones in the placenta supplements, compared to the placebo. Conclusions: Some hormones in encapsulated placenta lead to small but significant differences in hormonal profiles of women taking placenta capsules compared to those taking a placebo, although these dose–response changes were not sufficient to result in significant hormonal differences between groups. Whether modest hormonal changes due to placenta supplementation are associated with therapeutic postpartum effects, however, awaits further investigation.